Novel infrared-terahertz fusion 3D non-invasive imaging of plant fibre-reinforced polymer composites. (28th July 2022) - Hu, Jue; Zhang, Hai; Sfarra, Stefano; Santulli, Carlo; Tian, Guiyun; Maldague, Xavier
Abstract: The reinforcement of polymer composites using plant fibres has received vast and growing attention for investigation owing to their capability to serve as semi-structural materials, especially as a substitute for fiberglass. However, in this type of research, the structural complexity, due to geometrical mismatches and inherent variability to the properties of vegetable fibres and plant fibre composites would benefit from more effective non-invasive inspection techniques. In this work, a novel infrared-terahertz fused approach was proposed, and a new unsupervised deep residual fusion algorithm was developed in order to combine the outputs from two different physical mechanisms. Specifically, infrared imaging provided the details of the defects and the morphological information from the surface and subsurface, while terahertz imaging recorded the distribution of the fibres and the resin. Finally, the fused infrared-terahertz slices were reconstructed into a form of 3D exhibition for inspection and evaluation of two plant fibre-reinforced polymer composites in first time using multiphysical imaging and fusion. Graphical abstract: Image 1 Highlights: A novel infrared-terahertz fusion non-invasive imaging technique was proposed for 3D inspection. An unsupervised deep residual fusion algorithm was proposed to merge the information from terahertz and infrared. The proposed fusion imaging technique achieves high resolution and high contrast imaging on internal layers. The reconstructed 3D fusion slices with spatial resolution of 0.5 mm were compared with X-ray CT.